2011
DOI: 10.1016/j.molcel.2011.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of Drp1/Fis1 Availability by AKAP121/Siah2 Regulates Mitochondrial Adaptation to Hypoxia

Abstract: SUMMARY Defining the mechanisms underlying the control of mitochondrial fusion and fission is critical to understanding cellular adaptation to diverse physiological conditions. Here we demonstrate that hypoxia induces fission of mitochondrial membranes, dependent on availability of the mitochondrial scaffolding protein AKAP121. AKAP121 controls mitochondria dynamics through PKA-dependent inhibitory phosphorylation of Drp1 and PKA-independent inhibition of Drp1-Fis1 interaction. Reduced availability of AKAP121 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
231
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(254 citation statements)
references
References 32 publications
(46 reference statements)
15
231
1
2
Order By: Relevance
“…Components of the cAMP signaling cascade are also coordinated to regulate this process (see Cardiovascular disease panel). AKAP121 (also known as AKAP1) enables PKAmediated phosphorylation of dynaminrelated protein 1 (DRP1), which prevents it from associating with the fission factor FIS1 on the mitochondrial membrane (Kim et al, 2011). Hypoxia results in the increased expression and activity of the ubiquitin ligase SIAH2, which then ubiquitylates AKAP121, leading to its breakdown and consequent dephosphorylation of DRP1.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Components of the cAMP signaling cascade are also coordinated to regulate this process (see Cardiovascular disease panel). AKAP121 (also known as AKAP1) enables PKAmediated phosphorylation of dynaminrelated protein 1 (DRP1), which prevents it from associating with the fission factor FIS1 on the mitochondrial membrane (Kim et al, 2011). Hypoxia results in the increased expression and activity of the ubiquitin ligase SIAH2, which then ubiquitylates AKAP121, leading to its breakdown and consequent dephosphorylation of DRP1.…”
Section: Diabetesmentioning
confidence: 99%
“…Hypoxia results in the increased expression and activity of the ubiquitin ligase SIAH2, which then ubiquitylates AKAP121, leading to its breakdown and consequent dephosphorylation of DRP1. Upon its dephosphorylation, DRP1 is able to interact with FIS1 to trigger mitochondrial fission and apoptosis (Kim et al, 2011). Intriguingly, another AKAP, mAKAP, binds to the transcription factor hypoxia-inducible factor 1a (Wong et al, 2008).…”
Section: Diabetesmentioning
confidence: 99%
“…In addition, the knockdown of Siah2, but not Keap1, was shown to significantly attenuate the hypoglycemia-mediated reduction of Nrf2 expression [40] . Mitochondria are critical for cell survival, and their morphology is associated with susceptibility to cell death signals [41] . In ischemiainduced cardiomyocyte cell death, Siah2 regulates the availability of the mitochondrial scaffolding protein AKAP121 and subsequent mitochondrial dynamics.…”
Section: Baba K Et Al Novel Function Of Siah2 In Ros Metabolismmentioning
confidence: 99%
“…Notably, Kim et al demonstrated that AKAP121 was ubiquitinated and subsequently degraded in a manner dependent upon SIAH2. 42 Hence, regulation of AKAP121 by SIAH2 is a key nodal point in Drp1 activation and mitochondrial fission. Further, mice germ-lines deleted for SIAH2 had smaller infarcts and reduced incidence of cell death, which highlights the importance of the SIAH2-AKAP121 axis in the regulation of Drp1 and mitochondrial fission.…”
Section: Regulation Of Mitochondrial Fissionmentioning
confidence: 99%
“…Further, mice germ-lines deleted for SIAH2 had smaller infarcts and reduced incidence of cell death, which highlights the importance of the SIAH2-AKAP121 axis in the regulation of Drp1 and mitochondrial fission. 42 Regulation of Drp1 by Mitotic Kinases Aurora A and Cyclin B-CDK1 Coordinated fission and fusion of mitochondria is a critical step in normal cell division and proliferation. A recent study by Kashatus et al 29 provided new insight into the regulation of mitochondrial fission events during cell division.…”
Section: Regulation Of Mitochondrial Fissionmentioning
confidence: 99%